Analysis of Inventory As An Object of Fiduciary Security In Credit Agreements Juridical Philosophical And Sociological Review - Happy Trizna Wijaya; Made Warka; Krisnadi Nasution (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The development of the global economy is progressing rapidly in line with the dynamics of globalization. To support economic activities, large amounts of capital are required that are quick and easy to access. One of the ways to obtain such funds is by applying for credit through financial institutions. In the credit application process, collateral or security is typically required to guarantee the debt. One such object of fiduciary security is inventory. Inventory is a type of movable property that can serve as fiduciary collateral. This study aims to examine the concept of inventory as fiduciary collateral and to analyze its philosophical, juridical, and sociological foundations. The findings indicate that inventory, as fiduciary collateral, may include raw materials, goods in process, and finished goods. Philosophically, this type of collateral is based on a relationship of trust between creditor and debtor, particularly regarding the repayment of debt as agreed upon using the specified collateral.Juridically, the use of inventory as fiduciary collateral is regulated under Law Number 42 of 1999 concerning Fiduciary Security, specifically in the Elucidation of Article 6 letter c. The unique characteristic of inventory lies in its dynamic and transferable nature, which results in the principle of droit de suite (right of pursuit) not being applicable. This is further emphasized in Articles 20 through 24 of the Fiduciary Security Law. Sociologically, fiduciary security agreements involving inventory contribute positively to economic activities within society and support the realization of equitable, prosperous, and just welfare.